The Impact of E-WOM, Brand Image, and Product Attributes on Mitsubishi Commercial Vehicle Purchases - Hutomo Rusdianto; Caesar Zavraedo Zakinadio (Journal of Economics and Public Health, 2025)
This study aims to analyze the influence of electronic word of mouth (e-WOM), brand image, product quality, after sales service, and product design on the purchasing decisions of Mitsubishi commercial vehicles among consumers in the Former Residency of Pati. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed using a five point Likert scale and analyzed using multiple linear regression with the assistance of SPSS version 29. The results indicate that e-WOM, brand image, and product quality have a significant effect on purchasing decisions of Mitsubishi commercial vehicles. Meanwhile, after sales service and product design do not have a significant effect on purchasing decisions. These findings suggest that consumers prioritize digital information, brand reputation, and product quality over after sales service and product design in the decision making process. This study contributes to the development of marketing strategy literature by identifying key factors influencing purchasing decisions in the commercial vehicle sector.